Optimized electrochemical biosensor for human prostatic acid phosphatase - Bedatty Fernandes, Flavio C. [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier B.V., 2017)
An innovative and sensitive label-free electrochemical biosensor platform for detecting human prostatic acid phosphatase (hPAP) is proposed herein. The methodology uses impedance-derived immittance functions (ImFs) for monitoring the interfacial changes in a hPAP bio-recognition layer constructed using a self-assembled monolayer of PEGlate thiol (low-fouling materials) and 11-ferrocenyl undecanethiol (redox probe confined). We evaluated the response toward the target primarily in phosphatase-buffered saline, at varying concentrations and across a wide range of frequencies. The optimum frequency for each ImF parameter was selected based on its sensitivity and linearity within a target concentration ranging from 20 pM to 5000 pM and a limit of detection (LoD) below the cut-off value for this cancer biomarker (10 pM). The best ImF selected (inverse of imaginary capacitance, 1/C?) was then successfully used to monitor hPAP in human blood serum and showed a linear range from 50 pM to 104 pM, with an LoD of 11.2 +/- 2.6 pM. Additionally, both the assay and analysis of the results can be performed in a few minutes without the need to add an interfering redox probe to the biological samples, thus providing a rapid, sensitive, and label-free test for prostate cancer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Immittance spectroscopy; Electrochemical impedance spectroscopy; Prostate cancer; Human prostatic acid phosphatase; Label-free sensing; Electrochemical biosensora